UPAYA PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MEDIA PERMAINAN WORDWALL MATERI TERMOKIMIA PADA KELAS XI SMA - Rina Syadilla; Dinda Syuhada Afriani; Astriana Purba; Elsa Elperida Pandiangan; Monalisa Situmorang; Putri Andini; Marnida Yusfiani (STKIP Subang, 2026)
This study aims to improve students’ learning outcomes in thermochemistry through the implementation of Wordwall-based game learning media using the Teams Games Tournament (TGT) cooperative model. This research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 35 students of class XI-3 at SMA Negeri 10 Medan. The research instruments included learning outcome tests (pre-test and post-test), observation sheets, and student worksheets. Data were analyzed using descriptive quantitative methods with the N-gain test to determine the improvement in students’ learning outcomes. The results showed a significant improvement in learning outcomes from cycle I to cycle II. The percentage of learning completeness increased from 51.4% in cycle I to 94.3% in cycle II. The N-gain analysis also indicated an increase in students’ learning achievement categories. Therefore, it can be concluded that the implementation of Wordwall-based learning media through the TGT model is effective in improving students’ learning outcomes in thermochemistry.